Kerugian Negara Diakibatkan oleh Badan Usaha Milik Negara (BUMN) sebagai Kerugian Keuangan Negara: Penelitian - Budi Harianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This journal examines the analysis related to the review of the status of state financial losses caused by state-owned enterprises (BUMN) and the accountability mechanisms related to state losses, both unintentional and negligence committed by BUMN officials. The type of research conducted is normative legal research with a statutory approach, and legal history, as well as the existence of state finances. This research shows that the 1945 Constitution and the state finance law provide legal certainty regarding the state's financial status within the BUMN environment as the biggest supporter and supporter in providing capital to create mechanisms and governance so that there is very high state financial accountability. accountable and open.